An Oratory in the Figures of Speech of Somdej Phrabuḍhacharaya (Kiew Upaseṇo) - Moolarsar, Phra Boworn; Phiwhluang, Phramaha Atthaphong (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 11 No 1 (2019): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
The objective of this academic articles is to study the part of presentation strategy, the technique of composing rhetoric art and the speech acts strategy in Dharma preaching of Somdej Phrabuḍhacharaya in 9 Dharma books. The results from the study the part of presentation strategy found that preaching found that there were: 3 i.e. introduction, continuity and ending. Preachment found that there were: 4 i.e. title, introduction, continuity, and ending. The technique of composing rhetoric art found preaching have to use of friendly words, to create a new proverb and preachment have to use of informal language and Buddhist proverb. And 7 types of speech acts strategy i.e. speech act of asking, speech act of need, speech act of humor, speech act of order, speech act of warning, speech act of introduction and speech act of question